Pandora hearts. 09 - Mochizuki, Jun (Yen ; Little, Brown [distributor], 2012)
"The incuse on Oz Vessalius's chest ticks onward, but the young heir to one of the four great dukedoms directs his gaze back, seeking the facts behind a centuries-old tragedy. Intent on examining the ruins of Sablier despite warnings to scare him away, Oz and his makeshift party of explorers wander through the remnants of the former capital in search of clues to shed light upon the consuming darkness of the past. But in the yawning void where the opulent city once stood, will Oz come face-to-face with the truth? Or will he find misery the only resident?"--P. [4] of cover.